SYNTACTIC ANALYSIS OF NOUN PHRASE ON THE ENGLISH TRANSLATION OF SURAH AL-MULK (TREE DIAGRAM) - Muhamad Arsad; Asridayani Asridayani; Vera Magria (Universitas Muara Bungo, 2022)
Syntactic Analysis Of Noun Phrase On The English Translation Of Surah Al-Mulk (Tree Diagram) is a study that analyzes the forms and functions of noun phrases on The English Translation of Surah Al-Mulk (Tree Diagram) translated by Taqiud-din Al-hilali and Muhsin Khan. The objectives of this research are (1) to classify the forms of noun phrase on the English translation of Surah Al-Mulk; (2) to explainthefunctionsofnounphraseontheEnglishtranslationof Surah Al- Mulk. The writer used descriptive qualitative method because the research focuses on describing and exploring the forms and the functions of noun phrase on the English Translation of Surah Al-Mulk. In collecting the data, the writer used the theory of non-participant observation technique and then used the theory of content analysis technique to analyze the data. In order to make easier the readers, the writer explains the forms of noun phrases with tables and abbreviation code of tree diagram based on syntax rule. The data were words that contain noun phrases. After the data were collected, the data were classified and explained based on Eastwood’s theory (1994), that proposed some forms and functions of noun phrases.The result of the study reveals some findings: The writer found nine forms of noun phrases are contained in 133 data, then in 133 data consist of 168 data which is in one datum there are more than one form of noun phrase. The writer found 62 data that form one word, then the writer found 48 data modified by the determiners, 30 data modified by prepositional phrases, 12 data modified by clauses, 6 data modified by an adjective, 5 data modified by a gerund, 2 data modified by a noun, 2 data modified by an adverb phrase, and 1 datum modified by past participle. Then, the writer found four functions of noun phrases from five functions based on Eastwood’s theory. The four functions are contained in 133 data which the writer found 61 noun phrases function as the subject, 35 noun phrases function as the object, 22 noun phrases function as the prepositional object, and 15 noun phrases function as the complement. Therefore, the writer concluded that the dominant form of noun phrase found in the Surah Al-Mulk is a noun phrase be one word (N/Prop), then the dominant function of noun phrase found in the Surah Al-Mulk is as the subject